Pengaruh Latihan Split Squat Jump dan Standing Jump and Reach terhadap Kekuatan dan Power Otot Tungkai - Mahfuz (Universitas Negeri Semarang, 2016)
This study aims to examine about: the effects of exercise on the split squat jump, standing jump and reach, split squat jump dan standing jump and reach, limb muscle strength and power. The kind of research in use in this study is a quantitative with the quasi experimen. The results showed: (1) There is a significant effect of split squat jump's exercise toward the strength and power of leg muscle; (2) There is a significant effect of standing jump and reach's exercise toward the strength and power of leg muscle; (3) There is a significant differences of split squat jump, standing jump and reach's exercise toward the strength of leg muscle; (4) There is a significant differences of split squat jump, standing jump and reach' exercise toward the power of leg muscle, as well as the exercise of split squat jump is more effective to improve the strength and power of leg muscle. Based on the analysis of above can be concluded that there is an increase in the strength abd the leg power of muscle to each group experimen and a control group after given the exercise split squat jump and standing jump and reach in the look of test-t in addition there are diffrences in the influence of through MANOVA test and training program split squat jump more significant rather than the exercise standing jump and reach and a control group in improving the leg power of muscle.